2014
DOI: 10.4149/neo_2014_039
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia in gastrointestinal stromal tumors

Abstract: The primary cilium is a solitary, sensory, non-motile microtubule-based structure that arises from the centrosome and is projected from the surface of most human cells. The objective of the current pilot study was to conduct an investigation of presence and frequency of cilia in gastrointestinal stromal tumors (GIST).The presence of primary cilia in GIST was evaluated in 9 patients, including 8 primary tumors and 1 liver metastasis. In 2 patients the presence of primary cilia was evaluated not only in the prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…For IFT trafficking to occur, the microtubule plus-end directed motor kinesin-II (including KIF3A) and the IFT-B protein complex (including IFT52, IFT88, and IFT172) are necessary. We now show that these PC genes are expressed in GIST, consistent with previous reports that primary, recurrent, and metastatic GIST have PC [25, 26]. Thus, ICC and GIST have PC, which are important for Hedgehog and PDGFRA signaling; and GIST overexpress critical PC machinery involved in normal and aberrant PC signaling.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For IFT trafficking to occur, the microtubule plus-end directed motor kinesin-II (including KIF3A) and the IFT-B protein complex (including IFT52, IFT88, and IFT172) are necessary. We now show that these PC genes are expressed in GIST, consistent with previous reports that primary, recurrent, and metastatic GIST have PC [25, 26]. Thus, ICC and GIST have PC, which are important for Hedgehog and PDGFRA signaling; and GIST overexpress critical PC machinery involved in normal and aberrant PC signaling.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that two of these are Hedgehog target genes, namely, PTCH1 and HHIP , function as readouts of pathway activity, and act to fine-tune Hedgehog signals based upon negative feedback loops. Given the reported presence of primary cilia (PC) in GIST [25, 26], as well as the importance of PC in Hedgehog signaling transduction, it is also noteworthy that four proteins responsible for anterograde trafficking of cargo in PC, namely, KIF3A (encoding kinesin family member 3A), IFT52 (intraflagellar transport 52), IFT88 (intraflagellar transport 88), and IFT172 (intraflagellar transport 172), were significantly overexpressed in GIST as compared to ICC (Figure 3B). Overall, the top 7 overexpressed (>16-fold) genes in GIST relative to ICC (in descending order) are HIPK2 (homeodomain-interacting protein kinase 2), IFT52, FOXF1 (forkhead box F1), RB1 (retinoblastoma 1), PtTCH1, RAB23 , and TGFBR2 (transforming growth factor beta receptor II).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also found that in subpopulations of cells within human glioblastoma tumors are ciliated (Sarkisian et al, 2014) and human medulloblastoma cells critically rely on the establishment of primary cilia to drive Shh‐mediated cell division (Gate et al, 2015). The presence of primary cilia also been found in the spindle and epithelioid gastric gastrointestinal stromal tumors cells (Castiella et al, 2013; Dvorak et al, 2014), HeLa (human epithelial adenocarcinoma), and other cancer cell lines such as MG63 (human osteosarcoma; Kowal & Falk, 2015), though the significance of this persistent primary cilium in cancer cells still unclear.…”
Section: Primary Cilium Abnormal In Different Cancersmentioning
confidence: 99%